C++ and Java: A Comparative Study of the Most Popular Object-Oriented Programming Languages in Libyan Universities - Mohammed, Faiza Abdulsalam; Alhassan, Nawara Makhzoum (المجلة العلمية لكلية التربية, 2023)
The software has been experienced a large level of improvements by a lot of scientific researchers in this world. It can be considered as a set of some meaningful instructions written in a certain programming language. There are several programming languages which got comprehensive popularity like C, C++, C#, and Java. These languages are used to primarily evolve various applications. Object-Oriented Programming (OOP) languages, such as C++ and Java are one of the main three categories of programming languages. Most of the programmers always have a debate about choosing the best object-oriented programming language to help them develop their software applications. This review paper involves a comparison of C++ and Java with respect to some theoretical aspects to figure out the basic differences between them. Consequently, guide students to make a critical decision to choose the most applicable object-oriented programming language to develop their applications. The study has focused on both programming languages because they are taught in most of Libyan universities.